A comparative study between the effectiveness of actual and televised teaching method in 1st year ESEP students of Leyte National High School, Tacloban City - Balita, Christine Bernadette A.; Ruiz, Lucille Anne S. (2007)
This study was conducted to find out whether there is a significant difference between the effectiveness of actual lecture and televised teaching method in first year ESEP students of Leyte National High School Tacloban City. A total number of 88 respondents from the sections I-CALEYA and I-ROSE were subjected to 12 experimental sessions in which each section will underwent instruction of 6 General Science topics in alternating actual lecture and televised teaching. Pretests and posttests of the same items, only arranged differently, were given before and after each instruction. When the mean differences of these quizzes were obtained, all but one of the actual teaching results showed higher mean difference than that of teaching. However, when subjected to a t-test, only three out of six comparison showed a value greater than that of standard t value 2.000 at df=60 and alpha=.05. This result only partially support the hypothesis that there is no significant difference between the effectiveness of the two teaching modes. Also, at the end of all sessions a uniform unit test was given to both sections to test their overall retention of the topics. Scores were scrutinized through an item analysis of the unit test in the context of this study. Overall result is consistent with that of the quizzes showing three out of six comparisons dominated by the actual lecture method while only two was dominated by televised method and one showing no difference. These statistical results implies that although there is a tendency of getting higher scores when exposed to actual teaching method, still there is no significant difference between the effectiveness of the two modes of instruction.